Approximate Solution of the de la Vallée Poussin Problem for a Differential Equation of Neutral Type by the Projection-Iterative Method - Gabrel', O. M.; Mulyavka, O. H. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We solve the de la Vallée Poussin problem for a functional-differential equation by the projection-iterative method. We construct an algorithm, establish conditions sufficient for the convergence of the method, and present a computational scheme.